Elucidating and Mitigating Degradation Processes in Perovskite Light‐Emitting Diodes. Issue 48 (16th November 2020) - Andaji‐Garmaroudi, Zahra; Abdi‐Jalebi, Mojtaba; Kosasih, Felix U.; Doherty, Tiarnan; Macpherson, Stuart; Bowman, Alan R.; Man, Gabriel J.; Cappel, Ute B.; Rensmo, Håkan; Ducati, Caterina; Friend, Richard H.; Stranks, Samuel D.
Abstract: Halide perovskites have attracted substantial interest for their potential as disruptive display and lighting technologies. However, perovskite light‐emitting diodes (PeLEDs) are still hindered by poor operational stability. A fundamental understanding of the degradation processes is lacking but will be key to mitigating these pathways. Here, a combination of in operando and ex situ measurements to monitor the performance degradation of (Cs0.06 FA0.79 MA0.15 )Pb(I0.85 Br0.15 )3 PeLEDs over time is used. Through device, nanoscale cross‐sectional chemical mapping, and optical spectroscopy measurements, it is revealed that the degraded performance arises from an irreversible accumulation of bromide content at one interface, which leads to barriers to injection of charge carriers and thus increased nonradiative recombination. This ionic segregation is impeded by passivating the perovskite films with potassium halides, which immobilizes the excess halide species. The passivated PeLEDs show enhanced external quantum efficiency (EQE) from 0.5% to 4.5% and, importantly, show significantly enhanced stability, with minimal performance roll‐off even at high current densities (>200 mA cm −2 ). The decay half‐life for the devices under continuous operation at peak EQE increases from <1 to ≈15 h through passivation, and ≈200 h under pulsed operation. The results provide generalized insight into degradation pathways in PeLEDs and highlight routes to overcome these challenges. Abstract : A combination of in‐ and ex situ measurements are used to monitor the degradation processes in mixed‐halide perovskite light‐emitting devices. Device performance degradation is found to arise from accumulation of bromide at the interface between the perovskite and electron injecting layer, causing nonradiative recombination. Potassium halides mitigate the ionic movement and degradation, leading to better stability of devices under operation.